The impact of COVID-19 on the living and survival conditions of internally displaced persons in Burkina Faso. (March 2022) - Ozer, Pierre; Dembele, Adama; Yameogo, Simplice S.; Hut, Elodie; de Longueville, Florence
Highlights: This study is one of the first to explore how COVID-19 has affected the lives of IDPs in Burkina Faso. The socio-economic and humanitarian situation of IDPs has deteriorated substantially during the period of the lockdown. Within a few months, IDPs were trapped by a combination of new stresses: COVID-19, reduced humanitarian aid, and increasing malnutrition. This 'domino effect' resulted in mounting levels of insecurity and precariousness among the IDPs, which could in turn facilitate their recruitment by terrorist group. It is likely that this case study of IDPs in Kongoussi reflects the situation of many internally displaced persons around the world. Abstract: In recent years, as in other parts of the Sahel, the threat of terrorism has escalated in Burkina Faso. In 2019, this country hosted the fourth highest number of new conflict-related internal displaced persons (IDPs) in the world. These people have to cope simultaneously with the full spectrum of environmental, social and health-related stresses in the long, medium and short term, respectively. We seek to compare the living conditions of IDPs before and during the lockdown implemented by the authorities (between 27 March and 5 May 2020) to contain the spread of the virus. Interviews were conducted with 106 IDPs in Kongoussi (Central-Northern region). Although no respondent reported having been directly affected by the virus, 84.9% of the IDPs surveyed had no income-generating activities during the lockdown and the remaining 15.1% who continued to work reported that their activities had been greatly scaled-down. For a large majority of them, their living conditions, already described as difficult under 'normal' circumstances (insufficient food, insignificant financial assistance, or difficult access to health care), further deteriorated. In addition, IDPs were unable to leave the camps or regions where they were located to search for better living conditions or to return home. Lastly, 96.2% of respondents believed that the COVID-19 pandemic would have a negative impact on their future. These IDPs, like many in the sub-region and around the world, therefore require urgent assistance from the authorities and humanitarian NGOs, as the slightest new stress is likely to considerably worsen their already vulnerable state.